Measurement of Salivary Resistin Level in Patients with Type 2 Diabetes - Jinhua Yin; Hongfei Gao; Jing Yang; Lu Xu; Ming Li (International Journal of Endocrinology, 2012)
Serum resistin was initially hypothesized as a link between obesity and insulin resistance in mice. The latest evidence suggests that serum resistin is proinflammatory cytokines. Inflammation plays a key role in the pathogenesis of type 2 diabetes mellitus (T2DM). Many reports have previously identified changed serum resistin levels in patients with T2DM, but little is known of the levels of resistin in saliva. In our study, saliva and serum samples were collected from 38 patients with newly diagnosed T2DM at each time point of OGTT and 35 nondiabetic controls at fasting state. Resistin concentrations were measured using ELISA. We have demonstrated the presence of resistin in saliva of T2DM and nondiabetic subjects. Saliva resistin levels of T2DM are significantly higher than those of nondiabetic controls. Resistin levels in saliva are not affected by eating activity and correlated with serum resistin levels at any time points of OGTT. A positive correlation of serum and salivary resistin with BMI and HOMA-IR existed in T2DM. Measurement of resistin in saliva is a simple, noninvasive and may be an acceptable alternative to blood sampling for evaluatinginflammation/obesity/insulin resistance state.